Book reviews: Mark Elin, Simeon Reich and David Shoikhet, Numerical range of holomorphic mappings and applications, Cham: Birkhauser xiv + 229 p. 2019. ISBN 978-3-030-05019-1/hbk; 978-3-030-05020-7/ebook - COBZAȘ, Ștefan (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
Combining methods from various areas of mathematical analysis (understood in a wide sense - functional analysis, operator theory, operator equations, holomorphic vector functions) and presenting both classical results and new developments, many of the latter due to the authors, this fine book re ects the authors' encyclopedic knowledge of mathematics as well as their ability to present the results in an accessible and clear manner. The book sheds a new light on the numerical range of holomorphic mappings and its applications and invites people, especially young researchers, to push further research in these areas.